Hubungan Status Sosial Ekonomi dengan Perilaku Hidup Bersih Sehat (PHBS) Masyarakat di Desa Pajukukang Kabupaten Maros - Usman K, Rismalasari; Daud, Firdaus; Wiharto, Muhammad (Universitas Negeri Makassar, 2020)
Abstract. Healthy Clean-Living Behavior (PHBS) is carried out in order to realize a healthy life so as to prevent disease. The factors that cause the lack of people to behave in a healthy clean lifestyle are caused by their socioeconomic status. The socioeconomic status intended here is the level of education, type of work and income level. The purpose of this study was to determine how the condition of the socioeconomic status of the community and the behavior of healthy clean living in the community and to find out whether there is a relationship between socioeconomic status and healthy cleanliving behavior (PHBS) of the community in Pajukukang village, Maros district. This research is a correlation study. The sample taken was selected by cluster random sampling by taking a sample of 40 respondents per village. So that the overall sample of 120 respondents. Data were analyzed using descriptive and inferential data analysis. The relationship between education level and income level with PHBS was tested using Spearman rank, resulting in Asymp sig value. 0,000. Whereas the relationship of work type with PHBS was tested using contingency coefficients to produce Asymp sig. 0.010. Keywords: socio-economic status, healthy clean-living behavior, level of education, type of employment, level of income.